INITIATING PATIENTS ON GLP-1/COMBINED GLP-1 AND GIP AGONISTS: A QUALITY IMPROVEMENT PROJECT - Shreya Srivastava, MD, MPH (Elsevier, 2024)
Therapeutic Area: Diabetes Background: Both glucagon-like-peptide-1 (GLP-1) and combined GLP-1/glucose-dependent insulinotropic polypeptide (GIP) agonist medications have shown efficacy on weight loss, diabetes mellitus, and some with cardiovascular mortality benefits as seen with Semaglutide in the SELECT trial. However, these medications are prescribed at low rates despite the large number of patients who medically qualify. Methods: Patients who met criteria for prescription of GLP-1 and GLP-1/GIP agonist medications based on qualifying body mass index (BMI) and comorbid conditions were identified at the resident clinic of the Northwell Health Medical Subspecialities Clinic. A random sample of 500 of these patients underwent intervention. Chart review was performed to identify patients not presently prescribed the medication, and providers were notified via secure message. One year after pilot intervention, data was extracted from the electronic medical record regarding medication use, insurance, BMI, demographic factors, comorbid conditions, and laboratory values. Multivariate logistic regression analysis was conducted with adjustment for the above listed covariates. Results: Of the 500 randomly sampled patients, 43 were excluded due to missing key data. Of the remaining 457 patients, 32% were initiated on GLP-1 or GLP-1/GIP agonist medications (Table 1). Regression analyses revealed that patients with BMI greater than 35 had 2.79 and 5.88 larger odds, respectively, compared to those with BMI 30-35 and 27-30, of being started on the medication (95% CI 1.62 - 4.80, 3.04 - 11.38). Additionally, patients on metformin had 2.6 times greater odds of being started on the medication (95% CI 1.61 - 4.33). For every 1% increase in Hemoglobin A1c there was a 1.79 times greater odds of prescription (95% CI 1.45-2.19). Conclusions: Our study demonstrates that there is a significant proportion of patients with BMI less than 35 who qualify and may benefit from the use GLP-1 or GLP-1/GIP agonist medications. Providers should be aware of under-prescribing in this population in addition to those who have well-controlled diabetes.